Biosynthetic of Titanium Dioxide Nanoparticles Using Zizyphus Spina-Christi Leaves Extract - Tuqa B. Alobaidi (Polish Society of Ecological Engineering (PTIE), 2022)
The present project utilizes a straightforward, inexpensive, and environmental friendly approach to produce Titanium dioxide nanoparticles utilizing Zizyphus Spina-Christi leaves (Z-TiO2). Ultra-Spectrophotometry (UV-Vis) was used to characterize the synthesized nanoparticles, which showed the production of nanoparticles at 320 nm absorbance. To investigate functional groups, Fourier Transform Infrared Spectroscopy (FTIR) has been used. The presence of Titanium Dioxide was verified using Energy Distribution X-ray Spectroscopy (EDS). Surface area is calculated using the Brunauer Emmett Teller (BET) formula. Images from Field Emission Electron Microscopy (FE-SEM) verified the nanoparticles' spherical shape and relatively homogenous size distribution. These findings demonstrated that the production of Z-TiO2 nanoparticles was successful.